2012
DOI: 10.1177/0363546512455395
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography and Nerve Conduction Velocity for the Evaluation of the Infraspinatus Muscle and the Suprascapular Nerve in Professional Beach Volleyball Players

Abstract: Professional beach volleyball players have a high frequency of infraspinatus atrophy (34%) and significantly reduced shoulder strength of the hitting shoulder. These findings are not associated with demographic factors. Electromyography and NCV measurements suggest a suprascapular nerve involvement caused by repetitive strain injuries of the nerve. External rotation strength measurements and NCV measurements can detect a side-to-side difference early, while EMG may show compensation mechanisms for progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
(20 reference statements)
3
40
0
Order By: Relevance
“…The first specific study on the shoulder was published in 2009 (Lajtai et al, 2009), where prevalence of infraspinatus muscle atrophy in professional beach volleyball is of 30% of players. Years later, infraspinatus muscle atrophy is study more deeply (Lajtai et al, 2012), where a prevalence of 34% was established as a consequence of a repetitive traction injury of the suprascapular nerve. Other studies focused on shoulder have been studied with specific techniques for shoulders injuries (Monteleone et al, 2014), detecting cases of calcific tendinopathy, impingement, inflammation of the cuff and rotator cuff degeneration in Italian athletes in beach volleyball.…”
Section: Specific Injuriesmentioning
confidence: 99%
“…The first specific study on the shoulder was published in 2009 (Lajtai et al, 2009), where prevalence of infraspinatus muscle atrophy in professional beach volleyball is of 30% of players. Years later, infraspinatus muscle atrophy is study more deeply (Lajtai et al, 2012), where a prevalence of 34% was established as a consequence of a repetitive traction injury of the suprascapular nerve. Other studies focused on shoulder have been studied with specific techniques for shoulders injuries (Monteleone et al, 2014), detecting cases of calcific tendinopathy, impingement, inflammation of the cuff and rotator cuff degeneration in Italian athletes in beach volleyball.…”
Section: Specific Injuriesmentioning
confidence: 99%
“…More recently there has been an increasing interest in beach volleyball due to the fact that it became an Olympic sport in 1996, and still now few studies have focused on those athletes (Bahr and Reeser, 2003;Lajtai et al, 2009;Lajtai et al, 2012;Monteleone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating beach volleyball demonstrated that athletes present with shoulder injuries (Aagaard et al, 1997;Bahr and Reeser, 2003), infraspinatus muscle atrophy (Lajtai et al, 2009;Lajtai et al, 2012), high prevalence of calcific tendinopathy of rotator cuff (Monteleone et al, 2014) and unrecognized decreased strength of external rotation along with unspecific shoulder pain (Lajtai et al, 2009). These findings corroborate that shoulder structures have high overload demands in beach volleyball (Lajtai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromyography (EMG) and Nerve Conduction Velocity (NCV) are additionally used to determine the condition of the nerve branches of the suprascapular nerve, and the extent of the damage [30,37], with the disadvantage that the first may appear falsely normal if the pathology hasn't yet reached an advanced stage, at the specific point in time that the examination is performed [7].…”
Section: Diagnostic Imagingmentioning
confidence: 99%